PD-1/PD-L1 inhibitors plus chemotherapy versus chemotherapy alone for Chinese patients with advanced non-small-cell lung cancer: an updated meta-analysis based on phase 3 randomized controlled trials - Jianfei Zhang; Min Liu; Dongyang Li; Jiali Luo; Min Wang (World Journal of Surgical Oncology)
Abstract Background The combination of PD-1/PD-L1 inhibitors with chemotherapy (PC) has shown promise in treating advanced NSCLC. However, its added benefit over chemotherapy alone in Chinese patients remains unclear. We performed an updated synthesis of phase 3 randomized controlled trails (RCTs) to assess both therapeutic effectiveness and associated safety of PC therapy in this population. Methods We systematically searched six different databases for relevant publications. Only phase 3 RCTs enrolling Chinese individuals with advanced NSCLC, contrasting PC and standalone chemotherapy, were eligible. The main outcomes were overall survival (OS) and progression-free survival (PFS). Tumor responses and adverse effects (AEs) were assessed as secondary indicators. Results Eleven phase 3 trials including 3712 Chinese participants were analyzed. The PC group showed significant better OS (Hazard ratio [HR]: 0.65 [0.60, 0.72], P < 0.00001), and PFS (HR: 0.49 [0.46, 0.53], P < 0.00001). Better survival rate at 6 to 60 months was observed in those given PC. Presence of brain metastases and receiving pembrolizumab were associated with improved outcomes in the PC subgroup. Regarding tumor responses, PC led to longer duration of response (HR: 0.43 [0.36, 0.50], P < 0.00001), and a higher objective response rate (risk ratio [RR]: 1.60 [1.49, 1.72], P < 0.00001). However, PC group exhibited more AEs and immune-related AEs (irAEs) in all severity levels. Conclusion PIC may offer superior clinical benefits over chemotherapy alone in Chinese patients with advanced NSCLC, though with irAEs that warrants careful monitoring.